ANALYSIS OF FLAVONOIDS PLANT KOROLKOVIA SEVERZOVII (Scientific journal of the Fergana State University, 2024)
Korolkovia Severzovii presents a brief biological classification, alkaloid content and distribution, and analysis of flavonoid content in roots and aerial parts collected in the Angren Mountains region. The results of a comparison of the content of flavonoids in the root and aerial parts, as well as their significance in folk medicine, are described. A comparative analysis of studies carried out in the process of studying the composition of flavonoids, samples of spectral data and their analysis is given.